Scenic Arts in Second Language Learning: The Experience of ED-3091 Project: Strengthening of English Teaching and Learning - Salas Alvarado, Jonnathan (2019)
Language teaching, and particularly English teaching, have constantly evolved in terms of the methods and techniques used in the classroom. Language teachers have implemented a series of strategies seeking to innovate the teaching and learning process. In this article, scenic arts are presented as a possibility to diversify and enhance English learning. This article systematizes the experience of one of the activities developed within the project ED-3091: Strengthening English Teaching and Learning. This is an outreach program on the Pacific Campus of the University of Costa Rica. The experience of the English cultural-artistic gathering that organized the aforementioned project, in which 105 students from 4 schools of the Puntarenas region participated, is described. The article includes a reference to the project, a description of the activity itself, the dynamics as well as the participants’ perceptions about the academic potential of this type of activities. The opinions of the participants were very favorable and generated an interesting discussion around alternative teaching methods.